Esophageal Foreign Body Missed Diagnosis; an Analysis of 12 Cases - Xin Yan; Guoping Dai (Archives of Academic Emergency Medicine, 2023)
Missed diagnosis of foreign bodies in esophagus occasionally results in adverse consequences for patients. This study aimed to analyze the clinical characteristics of esophageal foreign body missed diagnosis in 12 cases. Among the 12 patients, 7 didn't undergo esophagus-related examination due to mild pain; One case didn't report a clear history of swallowing foreign bodies. For one case, computed tomography (CT) examination had not reached the esophageal foreign body level. Two cases were missed diagnosis because the foreign bodies were too tiny to develop clearly on CT. One case showed foreign body in esophagus during initial CT examination, but after subsequent gastroscopy, no foreign body was found. Among the 12 patients, 7 had esophageal perforation, 1 of which developed a neck abscess, and 1 had peri-esophageal abscess. It seems that, if foreign bodies in the pharynx or esophagus are suspected and no foreign bodies are found in the laryngoscope, chest CT scan is necessary. It is best to perform examination of full-length esophagus and pharynx, because foreign bodies may exist in the post-cricoid region or the deep part of the pyriform sinus, especially in older cases with longer retention times.